Chromosomal and structural anomalies in fetuses with open neural tube defects. (February 2014) - Ekin, A.; Gezer, C.; Taner, C. E.; Ozeren, M.; Ozer, O.; Koç, A.; Gezer, N. S.
<x xml:space="preserve">Abstract</x> The aim of this study is to evaluate the frequency and types of associated anomalies with the results of ultrasonographic and postmortem examination and identify the necessity of prenatal karyotyping among fetuses with open neural tube defects (NTD). Fetuses diagnosed with NTDs between 2008 and 2012 were retrospectively analysed. A total of 167 fetuses that were prenatally karyotyped, terminated and examined at postmortem were evaluated. Associated anomalies were detected and classified by detailed ultrasonography and autopsy findings. In total, 57 fetuses (34.1%) had associated anomalies. Prenatal ultrasonography detected 73.1% of additional anomalies compared with autopsy. Three fetuses had chromosomal abnormalities with multiple additional anomalies. A complete anatomical survey and genetic evaluation is needed for the fetuses with NTDs. We found lower chromosomal abnormality rates but due to some factors specific to NTDs, ultrasonography may not be predictive as to whether the fetus is isolated or not. We still therefore also offer chromosome analysis in isolated cases.